ANALYSIS OF COOPERATIVE RELATIONS OF FOREIGN FINANCIAL INSTITUTIONS WITH UZBEKISTAN (Academia Science Repository, 2023)
Foreign finance institutions international economic relationships in keeping countries by signed contracts based on to be built organizations is considered This type contracts based on existing global problems solve in order to countries and non-state institutions participation reach can Foreign finance institutions empty standing money funds fund in appearance forms. This funds to investment rotate through international financial intermediary as activity walking, money transfers and lending services through the real economy to the activity own effects they show